The Effects of Reinforcement and Punishment Magnitude on the Formation and Maintenance of Equivalence Classes. - Regaço, Alceu; Perez, William F.; Camargo, Julio C.; de Rose, Julio C.; de Souza, Deisy G. (Psychological Record, 2025)
Numerous studies have shown that simple discriminations are learned faster when punishment is used over positive reinforcement contingencies. However, to our knowledge, the use of punishment contingencies have not yet been investigated in the context of conditional discrimination training and equivalence class formation. This study aimed to assess the effects of different magnitudes of reinforcement and punishment on the formation and maintenance of equivalence classes. Fifty-six participants were assigned to three groups: More Reinforcement (MR), Balanced (B), and More Punishment (MP), differing in the number of points earned or lost for choosing the correct or incorrect comparison stimulus. Participants underwent relational training using a gamified matching-to-sample software and were tested for the emergence of three 3-member classes of abstract stimuli. After 7 days, participants were tested for the maintenance of the equivalence classes. The results revealed that a higher magnitude of punishment disrupted conditional discrimination learning and the emergence and maintenance of derived relations. The magnitude of the positive reinforcer did not affect participants' performance. This study highlights the need for new experimental studies exploring the effects of reinforcement and punishment on the formation and maintenance of equivalence classes.